2022
DOI: 10.3390/w14020162
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Groundwater Level under Climate Changes in the Gnangara Region, Western Australia

Abstract: The groundwater-dependent ecosystem in the Gnangara region is confronted with great threats due to the decline in groundwater level since the 1970s. The aim of this study is to apply multiple trend analysis methods at 351 monitoring bores to detect the trends in groundwater level using spatial, temporal and Hydrograph Analysis: Rainfall and Time Trend models, which were applied to evaluate the impacts of rainfall on the groundwater level in the Gnangara region, Western Australia. In the period of 1977–2017, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This decade-long drought severely affected Australia, particularly the southeast (King et al 2020). Problems caused by the long-term drought include dust storms, reduced surface water, well depletion, lower agricultural productivity, forest fires, and higher electricity prices (van Dijk et al 2013, O'Loingsigh et al 2015, Vliet et al 2016, Le Brocque et al 2018, Sheng and Xu 2019, Xu et al 2022.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This decade-long drought severely affected Australia, particularly the southeast (King et al 2020). Problems caused by the long-term drought include dust storms, reduced surface water, well depletion, lower agricultural productivity, forest fires, and higher electricity prices (van Dijk et al 2013, O'Loingsigh et al 2015, Vliet et al 2016, Le Brocque et al 2018, Sheng and Xu 2019, Xu et al 2022.…”
Section: Introductionmentioning
confidence: 99%
“…In Condamine, a sub-watershed system of MDB, Le Brocque et al (2018) observed decreasing groundwater trends, while Fu et al (2019) examined the roles of both climatic and non-climatic factors in groundwater replenishment in southeastern South Australia (SA). The impact of rainfall on groundwater in Western Australia's Gnangara region was explored by Kong et al (2022), who also considered the effects of vegetation and landforms. Further, analysis of the Murray-Darling Basin's (MDB) alluvial systems by Fu et al (2022) connected groundwater depletion with reduced rainfall and increased evapotranspiration.…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater level monitoring is essential for uncovering the spatial-temporal variation of groundwater levels in a studied aquifer, helping discussions on the sustainable use and management of groundwater resources. The spatial-temporal variation of groundwater levels in the aquifer is influenced by a variety of factors such as climate, hydrology, geology and human activities (Cui et al, 2020;Marques et al, 2020;Kong et al, 2022). The different hydrologic factors which can simultaneously play an important role in groundwater level fluctuations can be grouped into two groups: natural and anthropogenic.…”
Section: Introductionmentioning
confidence: 99%
“…However, this study made a unified assumption for the actual GWL of each slope element, which may lead to deviation in the calculated value and inaccuracy of the model [46]. Kong et al (2022) investigated the variation in the GWL using four trend analysis methods and its response and lag corresponding to rainfall by the HARTT model in the Gnangara region. However, the GWL needs no missing value and is continuous in time to meet the requirements of the model [47].…”
Section: Introductionmentioning
confidence: 99%
“…Kong et al (2022) investigated the variation in the GWL using four trend analysis methods and its response and lag corresponding to rainfall by the HARTT model in the Gnangara region. However, the GWL needs no missing value and is continuous in time to meet the requirements of the model [47].…”
Section: Introductionmentioning
confidence: 99%